The influence of studying abroad on word-production acquisition and intercultural growth of Indonesian EFL learner - Hanifah Hifni; Fahriany Fahriany (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2022)
This paper explores how an English Foreign Language learner who studies abroad acquires and develops her vocabularies according to the subjects’ perspective. The concept of studying abroad in the target language country can lead to the improvement of the language as well as the individual intercultural growth and perspective. Numerous statistical studies on the importance of studies abroad (SA) have mainly identified language acquisition as a successful way. Students who also lived abroad are exposed by other cultural environment, and therefore offering them to experienced cultural differences. Through the interpretation of the interview results, the research reports the learner’s word-knowledge development in the light of their studying abroad (SA) experience. One reason for anyone in learning foreign language is when they move out with their relatives in order to navigate with new worlds, new people, new cultures, and many other things of the country. This research shows that friends in the neighborhood and school contribute greatly to language development. The results showed that internal and external influences affected the English accomplishment of the participant. It turned out, the English proficiency influenced by intrinsic motivation, attitude, personality, cognitive style, and learning strategy. While the external influences of the participant were schooling, curriculum, motivation, and culture in her surroundings. The results show that motivation and anxiety are closely related to the English output.